Progress of UNAIDS 90-90-90 targets in a district in KwaZulu-Natal, South Africa, with high HIV burden, in the HIPSS study: a household-based complex multilevel community survey. Issue 11 (November 2017) - Grobler, Anneke; Cawood, Cherie; Khanyile, David; Puren, Adrian; Kharsany, Ayesha B M
Summary: Background: With the goal of eliminating new HIV infections, UNAIDS set the ambitious 90-90-90 targets to be achieved by 2020. We assessed whether these targets are being met among participants of the HIV Incidence Provincial Surveillance System (HIPSS) in a high-burden district of South Africa. Methods: We used data from a HIPSS household-based, cross-sectional survey of HIV prevalence and incidence done in the uMgungundlovu district, KwaZulu-Natal, in 2014 and 2015. In randomly selected enumeration areas, 50 households were drawn systematically along a serpentine pattern from a random start point. One eligible individual in each household was asked to provide blood for HIV testing and to complete a questionnaire. If a household refused to participate, the house next to it was approached. Eligible participants were aged 15–49 years, lived in the household, were not planning to move away, and spoke English or Zulu. Viral load was measured in samples positive for HIV. We also assessed participants' HIV linkage to care and treatment. Data were population weighted to allow for multilevel sampling and non-response. Findings: 9812 participants were enrolled, 3547 men (36%) and 6265 women (64%). Overall, 504 of 1014 men (estimate 52%, 95% CI 47–56) and 1833 of 2955 women (65%, 62–67) who were HIV positive knew their HIV status. Of those who knew, 344 of 522 men (69%, 63–75) and 1254 of 1845 women (70%, 68–73) were taking ART. Among recipients of ART, 294 of 341 men (85%, 80–90) and 1117 of 1249 women (90%, 87–92) had viral loads less than 1000 copies per mL. Among all HIV-positive participants, 427 of 1014 men (44%, 39–49) and 1680 of 2955 women (58%, 55–61) had viral loads lower than 1000 copies per mL. Interpretation: No UNAIDS 90-90-90 targets had been met in our study population. Major campaigns are needed to increase HIV testing, especially among men, and to ensure all HIV-positive patients are taking ART. Funding: Centers for Disease Control and Prevention and the US Presidents Emergency Plan for AIDS Relief (PEPFAR).